The fabrication of a label-free electrochemical immunosensor using an aldehyde-functionalized pyridinium salt for antibody immobilization. Issue 37 (2nd September 2016) - Zhang, Chunxiang; Pi, Yibing; Shen, Youming; Shen, Guangyu; Zhang, Youyu; Yao, Shouzhuo
Abstract : This paper reported a strategy based on the use of an aldehyde-functionalized pyridinium salt for the fabrication of a label-free electrochemical immunosensor. Abstract : This paper reported a strategy based on the use of an aldehyde-functionalized pyridinium salt for the fabrication of a label-free electrochemical immunosensor. The aldehyde-functionalized pyridinium salt was incorporated into Nafion to form a composite film modified on the surface of an Au electrode. The aldehyde-functionalized pyridinium salt was used to capture an antibody directly and improve the conductivity of the sensing interface, which ensured the convenient fabrication of a sensitive label-free electrochemical immunosensor for α-fetoprotein detection. Under optimal conditions, α-fetoprotein was detected in the range from 0.005 to 25 ng mL −1 with a detection limit of 0.003 ng mL −1 based on a signal-to-noise ratio of 3. This strategy would offer potential promise for the convenient fabrication of immunosensors and for clinical applications.